2018
DOI: 10.1007/s11276-018-1882-1
|View full text |Cite
|
Sign up to set email alerts
|

Potential effects on server power metering and modeling

Abstract: Cloud datacenters are compute facilities formed by hundreds or even thousands of servers. With the increasing demand of cloud services, energy efficiency of servers in data center has become a significant issue. The knowledge of the energy consumption corresponding to hardware and software configuration is important for operators to optimize energy efficiency of a data center. We currently work on a predictive model for energy consumption of a server, with inputs as service provided, hardware material equipped… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…Moreover, changing hardware components, such as the hard drive, the memory or even the power supply, does not affect the energy variation of a node, making it mainly related to the processor. This result was recently assessed by [26], where the rack placement and power supply introduced a maximum of 2.8 % variation in the observed energy consumption.…”
Section: Related Workmentioning
confidence: 85%
See 1 more Smart Citation
“…Moreover, changing hardware components, such as the hard drive, the memory or even the power supply, does not affect the energy variation of a node, making it mainly related to the processor. This result was recently assessed by [26], where the rack placement and power supply introduced a maximum of 2.8 % variation in the observed energy consumption.…”
Section: Related Workmentioning
confidence: 85%
“…Kistowski et al showed in [15] that identical processors can exhibit significant energy consumption variation with no close correlation with the processor temperature and performance. On the other hand, the authors of [26] claimed that the processor thermal effect is one of the most contributing factors to the energy variation, and the correlation between the CPU temperature and the energy consumption variation is very tight. This makes the processor temperature a delicate factor to consider while comparing energy consumption variations across a set of homogeneous processors.…”
Section: Related Workmentioning
confidence: 99%
“…As the power increases with the load, processor works harder and dissipates more heat, if the heat is not evacuated in time by the cooling system, the temperature surrounding processor becomes higher and leads to the rise of leakage current, which will in reverse increase the power of CPU [25] [26]. In the study of [6], the authors observed that leakage current of processor can contribute to over 30% power variation for server. However, there is doubt whether the samples have the same ability to evacuate the heat.…”
Section: How Thermal Effects Impact On the Consumption Of Servers?mentioning
confidence: 99%
“…On the contrary to dynamic power, static power is temperature sensitive value, but cannot be affected by frequency scaling. The consumption of the whole server can be then simply represented by the equation (5) and (6):…”
Section: B Hypothesis 2 : the Leakage Current Variationmentioning
confidence: 99%
See 1 more Smart Citation